Reproductive medicine and beyond - Wells, D (2011)
The 4th International Instituto Valenciano de Infertilidad (IVI) Congress, held in Valencia (Spain) at the beginning of April, followed in the footsteps of three previous congresses organized by the IVI network of fertility clinics. Over the years the meetings have grown in size and scope, mirroring the remarkable success of the IVI itself. The 4th IVI Congress was no exception, boasting a distinguished international faculty, addressing a broad range of subjects relevant to reproductive medicine. The meeting was divided into ten sessions and this article will attempt to give a flavor of the data presented and the conclusions reached in each. © 2011 Expert Reviews Ltd.